Intra-abdominal Sepsis After Ileocolic Resection in Crohn's Disease: The Role of Combination Immunosuppression. Issue 12 (December 2018) - McKenna, Nicholas P.; Habermann, Elizabeth B.; Glasgow, Amy E.; Dozois, Eric J.; Lightner, Amy L.
Abstract : BACKGROUND: Intra-abdominal sepsis complicates <10% of ileocolic resections for Crohn's disease, but the impact of combination immunosuppression and repeat resection on its development remains unknown. OBJECTIVE: The purpose of this study was to determine risk factors for intra-abdominal sepsis after ileocolic resection, specifically examining the role of combination immunosuppression and repeat intestinal resection. DESIGN: This was a retrospective review of patient records from 2007 to 2017. SETTINGS: The study was conducted at a single-institution IBD tertiary referral center. PATIENTS: Patients with a diagnosis of Crohn's disease who were undergoing ileocolic resection with primary anastomosis were included. Diverted patients were excluded. MAIN OUTCOME MEASURES: Preoperative and intraoperative variables, including preoperative immunosuppressive regimens and previous intestinal resection, were evaluated as potential risk factors for intra-abdominal sepsis. RESULTS: A total of 621 patients (55% women) underwent ileocolic resection for Crohn's disease; 393 (63%) were first-time resections. The rate of 30-day intra-abdominal sepsis was 8% (n = 50). On univariate analysis, triple immunosuppression (combination of a corticosteroid, immunomodulator, and biological) and previous intestinal resection were significantly associated with intra-abdominal sepsis. Both risk factors remained significant on multivariable analysis (OR for triple immunosuppression (vs none) = 3.53 (95% CI, 1.27–9.84); previous intestinal resection OR = 2.27 (95% CI, 1.25–4.13)). A significant trend was seen between an increasing number of these risk factors (triple immunosuppression and previous intestinal resection) and rate of intra-abdominal sepsis (5%, 12%, and 22% for 0, 1, and 2 risk factors; p < 0.01). A trend was observed between increasing number of previous intestinal resections and the rate of intra-abdominal sepsis ( p < 0.01). LIMITATIONS: This study is limited by its single-institution tertiary referral center scope. CONCLUSIONS: Combination immunosuppression and previous intestinal resection were both associated with the development of intra-abdominal sepsis. In light of these results, surgeons should consider the effects of combination immunosuppression and a history of previous intestinal resection, in addition to other risk factors, when deciding which patients warrant temporary intestinal diversion. SeeVideo Abstract athttp://links.lww.com/DCR/A664 .